SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF METHOD REALITIC MATHEMATICS EDUCATION ON MATHEMATICAL COMMUNICATION - Fitrah; Mira Ammelia Amri; Apit Dulyapit (SOSIOEDUKASI, 2026)
Mathematical communication ability is a fundamental competence in 21st-century education that enables students to reason logically, construct mathematical arguments, solve problems, and express ideas through verbal, written, and symbolic representations. This study conducts a Systematic Literature Review (SLR) to examine the impact of Realistic Mathematics Education (RME) on students’ mathematical communication ability. The review analyzed five empirical studies published between 2020 and 2025, selected through a systematic screening process based on predefined inclusion and exclusion criteria from major academic databases. The findings consistently indicate that RME improves mathematical communication ability by promoting contextual problem solving, multiple representations, collaborative discussion, and active student engagement. The principles of reality, level, intertwinement, activity, interactivity, and guidance collectively support students in explaining mathematical ideas and constructing meaningful arguments. In addition, several studies reported positive effects on learning outcomes, learning independence, and metacognitive reflection. However, the limited number of studies explicitly focusing on the relationship between RME and mathematical communication ability restricts the generalizability of the evidence. This review contributes to mathematics education by providing a synthesized understanding of current research trends and highlighting RME as a promising pedagogical approach for strengthening students’ mathematical communication ability while identifying directions for future research across broader educational contexts.